Türk Müziği'nde Akort Meselesi - Safkan, Gülay (Sosyal Bilimler Enstitüsü, 1997)
Türk Müziği'nde sabit bir referans sesinin olmamasından dolayı notasyonda makamlar bir yada iki ses üzerinde gösterilmekte, ancak farklı yerlerden transpoze edilerek çalınmaktadır. Transpoze edilerek yazılan bir nota ise icracı tarafından çalınamamaktadır. Böylece tonların tek başlarına önemi kalmamakta, kulak sesleri ayırt ederken bir tek yerden duymakta ve tonal kavramın gelişmemesine neden olmaktadır. Bu durumda bilimsel bir notasyonun varlığından bahsetmek de mümkün değildir. Enstrümanların gelişim gösterememesi ve kendi ses sahalarının dışında kullanılması, aynı şekilde insan seslerinin de kendi ses sahalarının dışında kullanılmaya mecbur bırakılması bu konuyla oldukça yalan ilişkilidir. Sonuç olarak, Türk Müziği'nde evrensel ölçüleri esas almak, gerek icra'da gerek notasyonda herşeyi bilimsellikle yerli yerine oturtmak gelişmenin ilk adımı olacaktır.

Music is a universal language to tell all the feellings of life with a great sensitivity. This language uses a terminology and the writing system which doesn't change from east to west and north to south. According to this people from different culture intergret each other's works without any dialog between each other moreover they can perform together. Music has a power that none of a language can reach. The determination of frequency of musical voices resulted by periodical vibration lies under this corporation. After the investigation of Diapozone by John Shore in 1711 Constant Frequency need was satishfied from the first part of 18th. century, Diapozone had several frequency for long time. This constant frequency voice: In 1788 in Paris "la" became 409 frequency in vienne - Berlin in 1850 "la" changed into 442. The la = 435 frequency in an international conference in Paris (1858) went on the same in an international conferance in vienne (1885). With an international contract in 1939 contact frequency sound accepted as la = 440 frequency by most of the Western countries. The reason of accepting "la" as a turing element; Because of being the most suitable sound among the sounds in the nature and beings in the most natural position. This sound is written in the hole between the second and third lines of this list with sol key and the place and the row of the other sounds, in another words the heights of them are organized by this sound. Different kind of instruments are made that gives only this sound to have the sound constantly. IV Among these whistle and brass band are not in good order. The best of them is the are made of stainless steel and called "sound dilemma (diapozone)". There is a tune system that is used all around the world la = 440 frequency. The musician tune their instrument according to the voice that is to be 440 vibrations in second (or it must be). In an orchestra piano is the only instrument that its tune doesn't change. Primarily, the constant reference voice is taken from piano by obue and the tunes of all instruments in the orchestra is done according to the obue. In an orchestra where there is no obue, it is providede to be met on the same tune by giving voice from tuned violin according to the constant reference voice. In Turkish music the instrument that can be reference to the tune is Kanun. But although the kanun takes the constant reference voice basicly it takes not for "la" fret in other words it takes for "re" fret. Namely, in the kanun "la" isnt 440 Hz. The reason for it is that, the constant reference voice which is accepted by the cummunity of Islam countries that Mr. Rauf Yekta attended in Syria, is not accepted for the reason of it is not suitable for Turkish music. And it is considerated basicly according to the diapozone that we call Bolahenk. Namely all the Turkish music instruments in an orchestra is a transpoze instrument in sol tone. Just like in the transpoze instrument in Western music as in fa tone korn, coranglais, alto flute in sol tone, the clarinet in "si flet", trumpet ect. But these instrument are made of different tones in connection with perform position, timbre and transposition features. This transpoze musical instruments gives a different voice from the written note when they are played. The Western do transpozes by writing its note. The work is determined by the composer about the played voice or in other words which key is going to be used and the transpoze musical instruments are played which is suitable for it. In Turkish music transpoze is done without using any key or without thinking of the note, name, by passing the string or changing the position. The tune system in Turkish music is determined with the names of the ney which is accepted to have 12 tones. Just like the names come out of Bolahenk tune from Bolahenk ney. In Turkish music the singers prefer the tunes which can notice their own color of voice. When the works are listened in the old records it is seen that the singers sang in Bolahenk tune even in more high pitched tune. It is observed that the instrumental musicians used the high pitched tune by pulling the tunes. In todays life lower tunes are preferred. (because of the reasons of microfone etc.) Today mostly the instrumental works, the tune that's suitable for every kind of instrument is called Bolahenk tune. But due to the ney's tall heiht small ney is used. However the small ney doesn't stisfy with it's voice and it's timbre, it's preferred kız ney or mansur in performing. The chorus generally prefer the kız ney tune. And there are chorus which prefer süpürde tune for more bright timbre. Whereas some chorus prefer mansur tune. The male solists generally sing from "süpürde" or kız ney tune. Sometimes they sing from müstahzen tune. VI It is observed that the female soloists mostly prefer Mansur tune. But at the same time they sing from kız ney tune. The instruments such as tambur, classical kemence, ud, kanun are voiced according to sol tuned diapozone called Bolahenk in Turkish music. It is sourced for not to be accepted the frequency of 440 "la voice" in the Turkish music. Where as it is accepted constant reference voice in the world. It is get out of the system especially with the instrument called "Ney". Although there is a "ney" used in Bolahenk tune totally there are so much ney. The transposition is very hard in this instrument. Besides to make easier of the playing position while performing ud the chord is lessen one sound, namely the ud with fa chord is sometimes used. Because of writing the melody on one point in the notation, a natural notation was developed, playing from different points contrivise as a tradition on condition that the notation being constant. The reason of its that; Turkish music is generally an oral music and there is a need to play from different points according to the performance of every kind of sound. Performer doesn't need a note that is made according to his voice whether the performer is a woman or a man it is played from different tones by looking the same notes. With this method the place of the note (according to Turkish music - Blohenk chord) is taken as a base due to this transpositions are made beginning from half sound to the seven sounds about the thick part and these are named considering the tones of ney. Among the transpositions it is played from the chord of süpürde, kız neyi and Mansur are mostly used as it is mentioned. Not having a constant reference sound results in not developing the concept of tone in Turkish music, instruments and the voice of the people are found theirselves vii far from the scientific classification. All the instruments and the colors of the voice should play and perform the melody that was written independently although it was written out of their own voice field. And the point that the small three - stringed kemence can't descent to the bass field soprano can be free to make the octave changes which is out of her voice field of course she is right here. Although there are quite important differences in the voice groups like soprano, alto, tenor, bas they perform the works from the same sound in the voice fields. Finally, our music is not the member of a common language. This condition causes not to be developed of tone concept. So absolutely it is not possible to bring up ears that hear. The member of the Turkish music hears every melody basically the notation of note name that he is accostomed to where ever. No matter where the melody is performed the member of the Turkish Music the name of the note which he hears takes as a principle that he is used to from one place of the notation can not be developed and a very big materials has been repeqted in a vicious circle. It forms the biggest reason why the instruments and the position concepts can not be developed. The instruments are obliged to be out of the voice fields. The human voice is used out of a scientific classification. It is performed with the voice groups that can not be come together in the structure of the single voiced music and sometimes it is let to the weaknesses occur in the timbre. In this condition, it can not be claimed about the existence of a scientific notation in Turkish Music. In order to participate in the polyphonic platform, to produce the orchestral structure of the suitable works in Turkish Music, is relatively closed with tune subject.
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 1997
Thesis (M.A.) -- İstanbul Technical University, Institute of Social Sciences, 1997
Keywords: Müzik; Akort; Müzik aletleri; Türk müziği; Music; Tuning; Musical instruments; Turkish music